Arduino + Android projects for the evil genius control Arduino with your smartphone or tablet - Monk, Simon; McGraw-Hill eBooks (New York, N.Y. : McGraw-Hill Education LLC., 2012)
Featuring two hot technologies, this book shows electronic hobbyists and experimenters how to create cool Arduino devices and use their Android smartphones and tablets to monitor and control them!
Create Android-controlled Arduino devices. Follow along with step-by-step instructions and detailed illustrations. Learn to use the Android Open Accessory Development Kit.
A. Evil genius$1!" (Bseries -- B. Dedication -- C. About the author -- D. Acknowledgments -- E. Introduction -- Arduino -- Android -- Arduino and android -- The book -- Projects -- Components -- Getting started -- A. Part one: android peripherals -- 1. Bluetooth robot -- Construction -- Theory -- Summary -- 2. Android geiger counter -- Google open accessory -- Construction -- Theory -- Summary -- 3. Android light show -- Construction: the droid accessory base -- Construction: the light show project -- Using the project -- Theory -- Summary -- 4. Tv remote -- Construction -- Using the project -- Theory -- Summary -- 5. Temperature logger -- Construction -- Using the project -- Theory -- Summary -- 6. Ultrasonic range finder -- Construction -- Using the project -- Theory -- Summary -- B. Part two: home automation -- 7. Home automation controller -- The sound link module -- Android software -- Internet access -- Theory -- Summary -- 8. Power control -- Power control electronics -- Constructing the power control module -- Adding it to the home automation controller -- Setting up your home -- Theory -- Summary -- 9. Smart thermostat -- Construction -- Using the system -- Theory -- Summary -- 10. RFID door lock -- Construction -- Using the system -- Theory -- Summary -- 11. Signaling flags -- Construction -- Theory -- Summary -- 12. Delay timer -- Construction -- Theory -- Summary -- C. Appendix: open accessory primer -- Learning android programming -- Arduino programming -- The example -- On the arduino -- Android -- Conclusion.s
Includes bibliographical references and indexes.
Also issued in online version.
Description based on cover image and table of contents, viewed on Mar. 13, 2015.
Keywords: Android (Electronic resource); Arduino (Programmable controller); Programmable controllers; Microcontrollers -- Programming; Home automation; Mobile computing; Electronic books